FAKTOR YANG BERHUBUNGAN DENGAN GIGI BERLUBANG PADA ANAK DI SDN 44 KOTA PALEMBANG - Melvani, Rizcita Prilia (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Parental behavior and habits regarding food, influenced by cultural factors, will influence a child's likes and dislikes regarding food. School-age children are in a developmental period where they are being fostered to be independent, behave in accordance with their environment, improve various abilities, and various other developments that require a healthy physique. Therefore, it is necessary to be supported by good nutritional conditions for optimal growth and development. This condition can be achieved through a process of education and habituation as well as providing appropriate needs, especially through daily food for a child. Tooth decay often occurs in children because children often eat sticky snacks and drinks containing a lot of sugar. This sticky nature determines the length of exposure to carbohydrates with bacterial plaque, especially in children at Elementary School 44, Palembang City. Using quantitative research methods, the number of samples used in this study was 60 children. The research instruments were questionnaires and dental examinations by community health center staff. Bivariate analysis used the chi-square test (α = 0.05). The study found a significant relationship between children's knowledge and sugary drink habits and tooth decay at Elementary School 44, Palembang City.